2022
DOI: 10.3389/fpubh.2022.1037412
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of compliance among patients with pediatric amblyopia undergoing virtual reality-based and traditional patching method training

Abstract: IntroductionThis study aimed to compare compliance between pediatric patients with amblyopia undergoing a smartphone virtual reality-based training method (EYEBIT) and those receiving traditional patching method training.MethodsA crossover design was adopted in this study. The enrolled children (n = 76) were randomized into the traditional patching and EYEBIT training method groups. The patients received training methods once a day for 2 h and 1 h in the patching and EYEBIT groups, respectively. Follow-up asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, the great advantage was that the subject’s compliance was complete. Additionally, the attractiveness of a game in comparison to patching has demonstrated its advantages for compliance when used for home-based training [ 32 ]. In our case, although the treatment was office-based, the attractiveness of an immersive VR game, along with the previous failure of patching in some cases, were strong motivating factors for compliance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the great advantage was that the subject’s compliance was complete. Additionally, the attractiveness of a game in comparison to patching has demonstrated its advantages for compliance when used for home-based training [ 32 ]. In our case, although the treatment was office-based, the attractiveness of an immersive VR game, along with the previous failure of patching in some cases, were strong motivating factors for compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 89 identified studies, the majority (n=69, 77.52%) used a quantitative study design, followed by mixed methods (n=14, 15.73%), [61][62][63][64][65][66][67][68][69][70][71][72][73][74] and a small number of studies utilized a qualitative study design (n=6, 6.74%). 24,[75][76][77][78][79] The findings of the scoping review indicated a preference for objective measurement and data analysis methods in the included studies.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…Nevertheless, the additional recovery of stereovision (3D vision) seems to require further ingredients in the training. Three studies have shown an improvement in stereovision in adults with amblyopia when using one game in a Virtual Reality (VR) environment [ 21 24 ], suggesting that a VR-based training providing 3D cues and rich feedback may better target improvement in stereovision in both strabismic and anisometropic type of amblyopia, improving also treatment compliance [ 25 ]. However, these preliminary studies in adults delivered the VR in a lab environment and with only one or two games.…”
Section: Introductionmentioning
confidence: 99%